Answer:
(4, - 2 )
Step-by-step explanation:
Given the 2 equations
x + y = 2 → (1)
x - y = 6 → (2)
Adding the 2 equations term by term will eliminate the term in y, that is
(x + x) + (y - y) = (2 + 6)
2x = 8 ( divide both sides by 2 )
x = 4
Substitute x = 4 in either of the 2 equations and solve for y
Substituting in (1)
4 + y = 2 ( subtract 4 from both sides )
y = - 2
Solution is (4, - 2 )
Answer:
48.
Step-by-step explanation:
33 + 15 = 48.
You can check your answer by subtracting 48-15, which gives you 33.
Distance between two points P(x1,y1), Q(x2,y2):
D=sqrt((x2-x1)^2+(y2-y1)^2)
Polygons are generally named in order along the perimeter, so that for a rectangle ABCD, AC or BD are diagonals.
Here, we need the distance between points A(4,3) and C(-4,-2)
Applying the above formula for distance between two points,
D=sqrt((4-(-4))^2+(3-(-2))^2)=sqrt(8^2+5^2)=sqrt(64+25)=sqrt(89)